Study of Secondary Metabolites of Azolla Microphylla as Candidates for Aedes Aegypti Mosquito Repellents - Pradana, Muhammad Sungging; Ekawati, Evy Ratnasari; Yusmiati, Siti Nur Husnul (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Dengue fever (DHF) is a disease that becomes an epidemic in an area every year. Prevention of the spread of DHF has been widely carried out as well as for vector bites. The use of repellent as one way to protect humans from mosquito bites. Alternative to the use of chemicals through the use of plants to repel mosquitoes need to be introduced. Mosquito repellents using plant-based ingredients have the advantage of being easily decomposed in nature. The aim of this study is to determine the content of secondary metabolites that can be used as mosquito repellents through multilevel extraction and to test the effectiveness of secondary metabolite content on the repellent power of Aedes aegypti mosquitoes. This study is an experimental study using 3 types of solvents with different levels of polarity. The results of the study obtained were positive for flavonoids with ethyl acetate solvent, positive for tepenoids and tannins with ethanol solvent. The positive compounds from the Azolla extract have the potential to repel mosquitoes.